Pengaruh Berbagai Variasi Volume Minyak Goreng Bekas Terhadap Standar Mutu Deterjen Cuci Cair - Dwi Rahma Wati; Bambang Suwerda; Rizki Amalia (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Cooking oil is a food ingredient that is used for daily needs. The re-use of cooking oil for many times is highly not suggested since it may lead to harm human health and pollute the environ-ment. One of efforts to process used cooking oil is to utilize it as base material in liquid detergent making. The purpose of the study was to know the influence of different volume variation of used cooking oil (i.e. 50, ml, 55 ml and 60 ml) toward the quality standard of the detergent yielded, referred to the SNI. The study was a pre-experiment with post-test only design and conducted in three replications. The laboratory measuremnet and panel test, showed that all of the liquid wa-shing detergent produced had fullfiled the standard parameter that consists of: homogenous liquid formation and can dripping, has perfume fragrance, has no-striking color, pH between 10-12, minimum active ingredient 25 %, specific weight between 1,2-1,5; and maximum microbe contamination 1x105. Results of subsequent statistical analysis using kruskal-wallis test at 5% signifcany level showed that the quality of all detergent yielded from the experiment were not significantly different, and 50 ml was decided as the most effective volume of the used cooking oil.